Case Report: Iatrogenic trauma of the bladder due to long-term unidentified intrauterine device malposition inside the bladder with rectovesical fistula [version 2; peer review: 2 approved] - Tjahjodjati Tjahjodjati; Dedi Rachmadi; Tengku Tania Zahrina; Nur Atik; Ahmad Agil (F1000Research, 2024)
According to reports, there are 1.9–3.6 incidences of IUD migration and uterine perforation for every 1000 IUD insertions. It is important to note that bladder perforation caused by a misplaced IUD is uncommon and is thought to happen most frequently during insertion. Here, we describe a patient who presented with symptoms related to the malposition of IUD inside the bladder. It is feasible to draw the conclusion that the cystoscopy technique should be taken into consideration as a suitable therapy option for such injuries in this organ. When a problem cannot be effectively treated by cystoscopy alone, laparotomy should be considered.